Association of SNCA variants with α-synuclein of gastric and colonic mucosa in Parkinson's disease. (April 2019) - Chung, Sun Ju; König, Inke R.; Lohmann, Katja; Hinrichs, Frauke; Kim, Juyeon; Ryu, Ho-Sung; Lee, Hyo Jeong; Kim, Kiju; Lee, Jeong Hoon; Jung, Kee Wook; Kim, Mi Jung; Kim, Mi-Jung; et al.
Abstract: Background: Alpha-synuclein (α-Syn) immunostaining in the enteric nervous system (ENS) has been investigated to determine the role of diagnostic biomarker of Parkinson's disease (PD). However, determining factors for alpha-synuclein (α-Syn) deposition in the ENS of humans are still unclear. We aimed to investigate a possible association between SNCA variants and the presence of α-Syn immunostaining in the ENS in patients with PD and healthy individuals. Methods: The study subjects consisted of 38 patients with PD and 46 healthy individuals. α-Syn immunohistochemistry was performed for gastric and colonic mucosal tissues of patients with PD and controls. Mucosal biopsy tissues of the ENS were obtained using standard biopsy forceps by endoscopic gastroduodenoscopy or colonoscopy. Two variants within the SNCA gene (the single nucleotide polymorphism [SNP] rs11931074 and the microsatellite REP1) were genotyped. Results: In patients with PD, the rs11931074 (G allele) was significantly associated with the presence of α-Syn immunostaining in the ENS (OR = 5.96, 95% CI = 1.70–20.97, P = 0.01). In an interaction analysis, SNP rs11931074–PD status interaction was significantly associated with positive α-Syn immunostaining in the ENS (OR = 7.33, 95% CI = 1.58–33.88, P = 0.01). Longer SNCA REP1 alleles were not associated with positive α-Syn immunostaining in the ENS. Conclusion: This exploratory study demonstrated that α-Syn deposition in the ENS may be associated with SNCA variants in patients with PD. Highlights: Determining factors for alpha-synuclein (α-Syn) deposition in the enteric nervous system (ENS) of humans are still unclear. SNCA rs11931074 (G allele) is associated with α-Syn immunostaining in the ENS in patients with Parkinson's disease (PD). α-Syn deposition in the ENS may be associated with SNCA variants in patients with PD.